Risk Factors and Outcomes for Conversion to Laparotomy of Laparoscopic Hysterectomy in Benign Gynecology. Issue 6 (December 2016) - Lim, Courtney S.; Mowers, Erika L.; Mahnert, Nichole; Skinner, Bethany D.; Kamdar, Neil; Morgan, Daniel M.; As-Sanie, Sawsan
Abstract : OBJECTIVE: To estimate the incidence and factors for conversion to laparotomy in women scheduled for laparoscopic hysterectomy for benign gynecologic indications and to examine the effect of conversion on patient outcomes. METHODS: A retrospective cohort study of a Michigan multicenter prospective database was abstracted from January 1, 2013, through July 2, 2014. Participants were collected from an all-payer quality and safety database maintained by the Michigan Surgical Quality Collaborative. Women with a preoperative indication of cancer or obstetric indications were excluded. A logistic regression model was used to calculate odds of conversion using patient preoperative and intraoperative attributes. RESULTS: During the study period, 6, 992 women underwent an attempted laparoscopic hysterectomy with 3.93% (n=275) converted to laparotomy. After adjusting for socioeconomic differences, hysterectomy indication, and intraoperative factors, there were decreased odds of conversion to laparotomy with use of robotic-assisted laparoscopy compared with traditional laparoscopy (adjusted odds ratio [OR] 0.14, 95% confidence interval [CI] 0.07–0.25) with a predicted risk of conversion of 0.8% compared with 5.4% ( P <.001). High-volume surgeons were less likely to convert to laparotomy compared with low- and medium-volume surgeons (adjusted OR 0.66, 95% CI 0.47–0.92) with a predicted risk of conversion of 1.4% compared with 2.25% ( P =.015). Conversion was associated with moderate or severe adhesive disease and increasing specimen weight. Conversion was associated with increased rates of surgical site infection, blood transfusion, severe sepsis, and reoperation. CONCLUSION: This analysis demonstrates that conversion to laparotomy is associated with increased odds of postoperative morbidity, and robotic assistance and surgeon volume are strongly associated with decreased odds of conversion. Abstract : Conversion to laparotomy of attempted laparoscopic hysterectomy is associated with increased odds of postoperative morbidity; robotic assistance and surgeon volume are strongly associated with decreased odds of conversion to laparotomy.